Dynamic Monitoring of Structural Deformations utilizing an Experimentally Validated Efficient Technique - El-Ashmawy, Khalid L. A.; El-Zareef, Mohammed A. (Engineering, Technology & Applied Science Research, 2023)
Up-to-date detection of a building’s responses under various load situations is essential to generate data used to assess its capacity to bear crucial loads. This study presents an innovative and effective method to detect structural displacements and provide a more accurate alternative to existing approaches such as trigonometry leveling and angle intersecting. The least squares method was used to produce a concurrent solution that includes all the observed data to improve precision and retrieve the data needed for statistical analysis. The proposed method was validated experimentally and compared with the total station, conventional structural analysis, and displacement gauges to test and monitor a three-point loaded Reinforced Concrete (RC) beam at seven discrete points. The displacement gauge measurements were used as a baseline for comparing the outcomes from the other methods. The maximum mid-span deflection of the tested RC beam showed that the variation between the recorded displacement using displacement gauges and the suggested approach was below 0.31mm, resulting in a 3.7% inaccuracy, while the total station observations and the ACI-Code deflection provisions provided deflections of 0.62 and 3.64mm, resulting in 7.4% and 43.4% inaccuracies, respectively. Furthermore, comparing the results using root-mean-square error, the suggested method’s precision in detecting displacements was much superior to the total station. The proposed approach was effective for detecting horizontal and vertical deformations and offers a viable option for building monitoring across both the element and whole building stages.